Implementing Accreditation Criteria of Undergraduate Academic Programmes Point of Views of Quality Departments’ Staff at the University of Benghazi. - عبد الحفيظ, د. عبدالسلام محمد; المصراتي, أ.سالمة مفتاح; بازينة , أ.حنان مصطفی (Dirasat in Economics and Business, 2021)
This paper aims to identify to what extent does University of Benghazi implement the criteria of undergraduate academic programmes from the point of views of quality departments’ staff at the university in terms of several aspects (i.e., education program, teaching staff, education support service, student affairs, utility, quality assurance and continues improvement). Adopting the quantitative method and using the questionnaire distributed to 30 heads of quality departments. The findings reveal that the implementing accreditation criteria are at medium level. The highest level of standards of programmes accreditation implementation is on the education support service and utility; followed by a teaching staff, student affairs, quality assurance and continues improvement. Regarding the education programme, it was at a low level. Some recommend- ations are presented; University of Benghazi should motivate the implementing of programme accreditation standards at all faculties and improve the academic programmes to satisfy the requireements of the labour market.